HALAL TOURISM: ANALYSIS OF RELIGIOSITY, MTES AND REVISIT INTENTION - Amalia, Rizki; Yahya, Afrida; Nurhalis, N (PEOPLE: International Journal of Social Sciences, 2019)
This study focus on halal tourism which examines religiosity, memorable tourism experiences (MTEs) and intention as indicators to develop halal tourism in Aceh. The aim of this study is to find out relationship between religiosity, MTEs, and intention with halal tourism.This study will be executed using quantitative method which employs structural equation modeling (SEM) techniques to analyze the data. Data collected using Likert scale questionnaire of 500 respondents. Respondents are international tourists who visit Aceh for halal tourism experiences who come from Malaysia, Singapore, Thailand, Brunei Darussalam. The result of this study will convince the importance of religiosity and MTEs to fashion new Aceh tourism focus for tourists who look for halal tourism experience. Thus, it will influence the intention of tourist to visit and revisit the place. Also, it can be utilized as recommendation for all stakeholders including government, tour operator, business owner, academia and local community to develop a much better halal tourism environment in Aceh. Therefore, Aceh will be famous and confirm itself as one of the best halal destination in Indonesia.The government of Indonesia has appointed several provinces as halal destination area and Aceh has been designated as one of the halal destination in Indonesia.